2011
DOI: 10.1111/j.1365-2036.2011.04759.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased lymphatic vessel density and lymphangiogenesis in inflammatory bowel disease

Abstract: SUMMARY BackgroundInvolvement of the lymphatic system in inflammatory bowel disease (IBD) has been suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 34 publications
1
68
0
1
Order By: Relevance
“…17 This fits well with evidence and discussion in CD that lymph drainage is impaired. 4,14,18 TLO formation as a feature of CD has been discussed previously. 19 However, because of the techniques applied herein and the fact that we have extended our analysis into the tissuedthe mesenteric adipose tissuedthat houses collecting lymphatic vessels, we have, for the first time, been able to associate TLOs with collecting lymphatic vessels, which are the major lymphatic vessels that normally supply LNs.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…17 This fits well with evidence and discussion in CD that lymph drainage is impaired. 4,14,18 TLO formation as a feature of CD has been discussed previously. 19 However, because of the techniques applied herein and the fact that we have extended our analysis into the tissuedthe mesenteric adipose tissuedthat houses collecting lymphatic vessels, we have, for the first time, been able to associate TLOs with collecting lymphatic vessels, which are the major lymphatic vessels that normally supply LNs.…”
Section: Discussionmentioning
confidence: 74%
“…In CD specimens prepared using similar approaches, lymphatic capillaries could be seen to have expanded significantly around blood vessels ( Figure 2G), fitting with previous literature that reveals lymphatic capillary expansion within the mucosa as well. 14 Collecting vessels were routinely difficult to identify in CD specimens, perhaps in part because of their weaker staining intensity in the midst of an expanded lymphatic capillary network.…”
Section: Lymphatic Changes In Crohn Diseasementioning
confidence: 99%
“…115,120 Although increased density of lymphatics is a characteristic of experimental and clinical IBD, lymphatic vessel dilation and edema formation in IBD could also be a consequence of impaired contractile function of the intestinal lymphatics. 121,122 In rat and guinea pig models of intestinal inflammation, indeed, the contractile capacity within isolated collecting mesenteric lymphatics is compromised, and this effect correlates with lymphatic dysfunction, lymphatic vessel dilation and mucosal inflammation. 88,103,123,124 Furthermore, these studies have shown cyclooxygenase (cyclooxygenase 1/2) or inducible nitric oxide synthase inhibitors improve lymphatic pumping in non-contracting lymphatics in experimental IBD, suggesting prostanoids and nitric oxide released during intestinal inflammation contribute to diminished lymphatic contractile activity.…”
Section: Roles Of Lymphatics In Inflammationmentioning
confidence: 99%
“…To assess whether lymphangiogenesis occurs in human IBD, we performed immunohistochemical staining of control and active CD-and UC-involved colons with antibodies recognizing podoplanin, a widely accepted marker of lymphatic vasculature (9,10,35). Normal colon mucosa only showed sporadic, thin LVs in the lamina propria and submucosa, whereas CD and UC tissues contained numerous, readily detectable dilated LVs ( Figure 1A).…”
Section: Density and The Vegf-c/vegfr3 Pathway Are Altered In Actimentioning
confidence: 99%